Poder e política no Brasil Imperial : traços da gênese e da trajetória dos Fontes e dos Dantas no Sertão da Bahia e de Sergipe Del Rey (1820-1850) - Andrade, Maristela do Nascimento (2017)
This work presents an analysis about power and politics in imperial Brazil as it seeks to show the traces the genesis and trajectory of two families in the backcountry of Bahia and Sergipe: the Fontes and the Dantas, which constituted powerful groups that accomplished regional importance by the confluence of political action and marriage arrangements. The research analyzes the literature pertinent to the object and printed sources and manuscripts from the nineteenth century located in the Instituto Histórico e Geográfico de Sergipe, in the Arquivo do Judiciário, in the Arquivo Público de Sergipe (Aracaju/SE), in the Arquivo do Barão de Jeremoabo (Itapicuru/BA), in the Paróquia Nossa Senhora da Piedade – (Lagarto/SE), in the Associação Nacional dos Professores de História, in the Arquivo Público do Estado da Bahia (Salvador/BA), in the Arquivo Público do Judiciário do Estado de Sergipe (Aracaju/SE), in the Biblioteca Nacional (Rio de Janeiro/RJ) and in the Instituto Geográfico e Histórico da Bahia. The text outlines the political transformations that have occurred in Portuguese America and its reflections in the sertão of Sergipe, and especially of Bahia; identifies the main agents of the spaces of power and their politic and social participation and highlights the efforts of a family to remain active in the public sphere.